Systematic Monitoring of Operation of Mining Companies and Branches (The Australasian Institute of Mining and Metallurgy, 2010)
One of the important directions of further increase of quality and efficiency of control of mining companies and branches is the creation of the operation and development monitoring systems of such facilities. The main purpose of these systems is to provide managers with reliable and timely information on the current state and typical tendencies of operation of the facilities under control. However until the present time no scientific and methodical ground for system monitoring of the mining companies and branches has been created. Therefore, the authors of the report have aimed to assess the current situation with regard to the researches in this field and to do analysis of the most important aspects and ways of solution of the issue under consideration.